PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE UNTUK MENINGKATKAN LITERASI DIGITAL SISWA SMP - Rosita, Dewi; Isnaynun, Isnaynun; Andrea, Reza; Pratama, Angga (Jurnal Muara Pendidikan, 2025)
The limited use of engaging and interactive learning media during the learning process, particularly in the subject of informatics at junior high schools, has reduced students' interest in learning. One application of technology in the field of education is the development of a website as an e-learning medium. This study aims to determine the feasibility level of website-based learning media and analyze the level of digital literacy among junior high school students. This research is a development study (R&D) using the Brog and Gall model, which includes the stages of needs analysis, planning, initial product development, validation, testing, first product revision, second product revision, effectiveness testing, and dissemination. The results of the study from material expert validation showed a score of 4.7 in the "Very Feasible" category; from three media experts, a score of 4.8 in the "Very Feasible" category; and from students, a score of 4.6 in the "Very Feasible" category. Overall, the results obtained a score of 4.6 in the "Very Feasible" category. Furthermore, the analysis of digital literacy levels among 102 junior high school students showed a Digital Skill score of 82% in the "Very High" category, a Digital Safety score of 71% in the "High" category, a Digital Ethics score of 83% in the "Very High" category, and a Digital Culture score of 82% in the "Very High" category.